Association between Malondialdehyde, GSH/GSSG Ratio and Bone Mineral Density in Postmenopausal Women - Innawati Jusup; Lusiana Batubara; Dwi Ngestiningsih; Faizah Fulyani; Devina Afraditya Paveta; Putri Theresia Lemmo Ate Bancin (Molecular and Cellular Biomedical Sciences, 2021)
Background: Osteoporosis is one of chronic degenerative diseases especially in postmenopausal women, characterized by a decreased bone mass due to imbalance activity between osteoblasts and osteoclasts. Recently, oxidative stress is believed to play an important role in osteoporosis pathogenesis. Oxidative stress is commonly considered as the consequence of an imbalance between pro and antioxidants species, which results in damage in the affected tissue. Malondialdehyde (MDA) is frequently used as a biomarker of oxidative stress in many health problems since MDA is produced at high levels during lipid peroxidation. Meanwhile, glutathione is well known as one of antioxidant which against oxidative stress by preserving its homeostasis in the reduced form of glutathione sulfhydryl (GSH) and the oxidized form of glutathione disulphide (GSSG). This study was aimed to determine the association between MDA, GSH/GSSG ratio and bone mineral density (BMD) in postmenopausal women.Materials and method: We conducted a cross-sectional study in 40 postmenopausal women. MDA and GSH/GSSG ratio were assessed by enzyme-linked immunosorbent assay (ELISA). Bone mineral density (BMD) was obtained from secondary data. The statistical analysis was conducted using Spearman rho’s correlation test.Results: Based on the test, we didn’t found significant correlation between MDA and BMD (r=-0.054, p=0.741), but we found significant moderate correlation between GSH/GSSG ratio (r=0.436, p=0.005) and BMD in postmenopausal women. Conclusion: There was no correlation between MDA and BMD in postmenopausal women. However, there was significant moderate correlation between GSH/GSSG ratio and BMD in postmenopausal women.Keywords: MDA, GSH/GSSG ratio, BMD, osteoporosis